CARACTERES MACROMORPHOLOGIQUES DES SOLS DEVELOPPES SUR FONDS VOLCANO-SEDIMENTAIRE AU BLAFO-GUETO (TOUMODI) DANS LE CENTRE-SUD DE LA COTE D’IVOIRE - Nestor, Kouakou Yao Kouman; Fernand, Yao Guy; Yves, Nangah Krogba; Derving, Baka; Achille, Adingra; Yao-Kouame, Albert (European Scientific Journal, ESJ, 2013)
In order to appreciate the current status of developed soil in the manganese and gold-bearing region of Blafo-Gueto at the Center-South part of Côte D’Ivoire, this study is undertaken and concerned some macromorphological parameter characterization. Based on the field description of these macromorphological parameters, by opening soil profile through two lines, the one on the hill Blafo, the other one on the hill Guéto, it was shown that the soil are reshaped and in brown color. The soil structures are lumpy in humus horizons which go to 30-40 cm. On the other hand, the structure is polyhedral subangular in intermediate and deep horizons. The drainage class is good in the humus or surface horizons and all the soil texture goes from sandy clayey to clayey soil. The percentage of the unrefined elements is beyond 60 and the hydromorphic spots, signs of a bad internal drainage begin to appear from the intermediate or accumulate horizons.